(untitled) (Bulletin of criminological association of Ukraine, 2025)
The article carries out a comprehensive doctrinal and methodological study of codification of legislation as a tool for stabilizing the legal space in the context of legal turbulence characterized by increased dynamics of regulatory changes, fragmentation of the regulatory framework and growing lack of legal certainty. It is proved that codification is not a purely technical and legal procedure, but is a conceptual mechanism for structural restructuring of the regulatory system aimed at restoring its internal logic, hierarchical consistency and axiological content. The author examines the impact of legal instability on the regulatory architecture of legislation and identifies the typical challenges faced by lawmakers in the context of a transitional period. The author emphasizes that effective codification requires a deep methodological foundation, which includes not only an analysis of the current regulatory framework, but also consideration of legal values, socio-cultural context and strategic guidelines for the development of the legal system. The author concludes that codification performs not only the function of systematization of norms, but also serves as an instrument of legal reconfiguration capable of restoring normative integrity, stability and predictability in the context of legal turbulence, and also promotes the rule of law as a basic value of a democratic society.